High-Resolution Mapping of the Folding Transition State of a WW Domain. Issue 8 (24th April 2016) - Dave, Kapil; Jäger, Marcus; Nguyen, Houbi; Kelly, Jeffery W.; Gruebele, Martin
Abstract: Fast-folding WW domains are among the best-characterized systems for comparing experiments and simulations of protein folding. Recent microsecond-resolution experiments and long duration (totaling milliseconds) single-trajectory modeling have shown that even mechanistic changes in folding kinetics due to mutation can now be analyzed. Thus, a comprehensive set of experimental data would be helpful to benchmark the predictions made by simulations. Here, we use T-jump relaxation in conjunction with protein engineering and report mutational Φ -values ( ΦM ) as indicators for folding transition-state structure of 65 side chain, 7 backbone hydrogen bond, and 6 deletion and /or insertion mutants within loop 1 of the 34-residue hPin1 WW domain. Forty-five cross-validated consensus mutants could be identified that provide structural constraints for transition-state structure within all substructures of the WW domain fold (hydrophobic core, loop 1, loop 2, β-sheet). We probe the robustness of the two hydrophobic clusters in the folding transition state, discuss how local backbone disorder in the native-state can lead to non-classical Φ M ‐values ( Φ M > 1) in the rate-determining loop 1 substructure, and conclusively identify mutations and positions along the sequence that perturb the folding mechanism from loop 1-limited toward loop 2-limited folding. Graphical abstract: Highlights: Folding kinetics of a comprehensive set of hPin1 WW mutants, spanning the whole sequence and multiple substitutions at many sites, has been studied. A very conservative phi-value analysis, identifying and excluding disruptive mutations, has revealed the interplay between loops 1 and 2 in the transition state in unprecedented detail. Unusually large "non-classical" phi-values are now explained by local native-state disorder. This comprehensive experimental data set will be valuable for comparison with molecular dynamics simulation, and we begin by creating a hybrid phi-value map for FiP WW domain for comparison with recent all-atom simulations.